Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/ele.13574
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying impacts of plastic debris on marine wildlife identifies ecological breakpoints

Abstract: Quantifying sublethal effects of plastics ingestion on marine wildlife is difficult, but key to understanding the ontogeny and population dynamics of affected species. We developed a method that overcomes the difficulties by modelling individual ontogeny under reduced energy intake and expenditure caused by debris ingestion. The predicted ontogeny is combined with a population dynamics model to identify ecological breakpoints: cessation of reproduction or negative population growth. Exemplifying this approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 75 publications
0
33
0
Order By: Relevance
“…These results could be explained by the fact that the accumulation of ingested microplastics in the digestive tract of fishes may lead to malnutrition and eventual starvation (Boerger et al, 2010), and consequently lower energy intake. This could mean less energy and resources allocated to the fundamental physiological processes of growth and reproduction (Marn et al, 2020). Yin et al (2019) reported that, in order to maintain normal functions under stressful conditions, black rockfish exposed to polystyrene showed significant reduction of available energy for growth through increased metabolic demands, while a reduction in protein content was observed as well.…”
Section: Discussionmentioning
confidence: 99%
“…These results could be explained by the fact that the accumulation of ingested microplastics in the digestive tract of fishes may lead to malnutrition and eventual starvation (Boerger et al, 2010), and consequently lower energy intake. This could mean less energy and resources allocated to the fundamental physiological processes of growth and reproduction (Marn et al, 2020). Yin et al (2019) reported that, in order to maintain normal functions under stressful conditions, black rockfish exposed to polystyrene showed significant reduction of available energy for growth through increased metabolic demands, while a reduction in protein content was observed as well.…”
Section: Discussionmentioning
confidence: 99%
“…Almost 700 aquatic species in the world were adversely affected by the introduction of microplastics, including sea turtles, penguins, and other crustaceans (Marn et al 2020). However, the predicament due to microplastic depreciates as most sufferers go unexplored over the vast oceans (Pabortsava and Lampitt 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One-way traps can arise when the novel element introduced in the environment (in this case plastic), mimics a traditional cue from habitat choice, thereby misleading the organism. Post-hatchlings occupy habitats that in the past were ideal locations for growth, however, these are now accumulating high abundances of plastic debris; potentially lowering survivorship and causing sub-lethal impacts on growth and maturity (Marn et al, 2020). Indeed it has been shown that plastic ingestion can create change in relation to nutrient acquisition and fitness consequences in marine turtles (Machovsky-Capuska et al, 2020) and be associated with pathology (Ryan et al, 2016) and potentially morbidity or mortality (Stamper et al, 2009;Poppi et al, 2012;Santos et al, 2015;Orós et al, 2016).…”
Section: Juvenile Marine Turtles and Plastic Pollution In Context Of Evolutionary Trapsmentioning
confidence: 99%
“…While plastic ingestion has been linked to morbidity and mortality (Stamper et al, 2009;Poppi et al, 2012;Santos et al, 2015;Orós et al, 2016;Wilcox et al, 2018), it is particularly difficult to attribute mortality (Bjorndal et al, 1994) especially when few studies corroborated marine debris ingestion with associated pathology. Moreover, the effects on sea turtles, including sub-lethal impacts such as exposure to persistent organic pollutants (POPs) via marine plastics are not wellunderstood (Clukey et al, 2017b;Marn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%